Rethinking Forest Tourism Governance in Indonesia: Ecological Justice, Legal Reform, and the Sustainable Development Goals - Elizabeth Ayu Puspita Adi; Bayu Ardhiansyah (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2026)
Indonesia's forest tourism governance is still plagued by overlapping regulations, fragmented institutional coordination and poor community participation. These issues compromise both ecological sustainability and social justice. This research aims to analyse the weaknesses of the current legal and institutional framework governing forest tourism, and to propose a governance model based on ecological justice that is aligned with the Sustainable Development Goals (SDGs). This study employs a normative legal approach, complemented by socio-legal and historical-legal analyses. Statutory regulations and legal doctrines are examined alongside the historical evolution of forestry law, and governance practices and policy implementation are critically assessed. Three main findings emerged from the results: first, a lack of regulatory coherence across sectoral laws governing forest tourism; second, the marginalisation of ecological justice and participatory governance principles; and third, the predominance of technocratic and market-oriented regulatory instruments that undermine conservation objectives. Although recent legal reforms provide partial reinforcement, they fail to address fundamental governance gaps. It can therefore be concluded that forest tourism governance requires an integrative legal reform model combining ecosystem-based conservation, community-based resource management, and polycentric institutional arrangements, in order to strengthen ecological integrity, institutional accountability, and community inclusion, and to advance SDGs 13, 15, and 16.